New Advances in the Determination of Free and Bound Phenolic Compounds of Banana Passion Fruit Pulp (Passiflora tripartita, var. Mollissima (Kunth) L.H. Bailey) and Their In Vitro Antioxidant and Hypoglycemic Capacities - Elisa Giambanelli; Ana Maria Gómez-Caravaca; Arancha Ruiz-Torralba; Eduardo Jesús Guerra-Hernández; Jorge Geovanny Figueroa-Hurtado; Belén García-Villanova; Vito Verardo (MDPI AG, 2020)
Banana passion fruit (Passiflora tripartite L.H. Bailey) is a lesser known species of the genus Passiflora. This fruit typically grows in the Andean region of Ecuador and it is locally known as tumbo, taxo or curuba. The juice of this fruit is highly appreciated in South America. Extracts of banana passion fruit were characterized for their content levels of free and bound phenolic compounds by high performance liquid chromatography coupled to high resolution mass spectrometry detector (HPLC-ESI-TOF-MS). A total of 82 polar compounds classified as phenolic acid derivatives, organic acids, benzophenones, flavan-3-ols, flavonols and flavones were detected in the extracts. The total phenolic content was 2356 mg 100 g−1 dry matter, with the bound phenolic fraction representing 37.7% of total amounts. Flavan-3-ols, such as (epi)catechin, (epi)azfelechin and their derivatives, were the main phenolic compounds in the free phenolic fraction; however, phenolic acids represented the most abundant class of bound phenolic extracts. The antioxidant and hypoglycemic capacities reported for banana passion fruit were higher than for other fruits. To our knowledge, this is the first time that bound phenolic compounds have been described in banana passion fruit pulp.